Gas permeation properties and characterization of mitrimid based carbon tubular membrane - Sazali, Norazlianie (2015)
Carbon membranes offer high potential in gas separation industry due to its highly selective. Therefore, this study aims to investigate the effect of carbonization parameter such as polymer composition, carbonization temperature, and carbonization environment on the gas separation properties. Polyimide (Matrimid 5218) was used as a precursor for carbon tubular membrane to produce high quality of carbon membrane via carbonization process. The polymer solution containing 5wt%, 10wt%, 13wt%, 15wt%, and 18wt% of Matrimid are prepared based carbon tubular membrane. The polymer solution was coated 3 times on the surface of tubular ceramic tubes by using dip-coating method. Dip-coating technique offer high potential in fabricating defect free carbon membrane. The polymer tubular membrane was then carbonized under nitrogen or argon atmosphere at temperature of 600, 750, and 850 oC with heating rate of 2 oC/min. Matrimid-based carbon tubular membranes were fabricated and characterized in terms of its structural morphology, chemical structure, thermal stability, and gas permeation properties by using scanning electron microscopy (SEM), Fourier transform infrared (FTIR), thermal gravimetric analysis (TGA), and pure gas permeation system, respectively. From the results, it is found that the best polymer composition was 15wt% while the best carbonization temperature for the preparation of carbon membrane-based Matrimid 5218 was at 850 oC. The highest CO2/CH4 and CO2/N2 selectivity of 83.30 and 75.73, was obtained for carbon membrane prepared under nitrogen environment. Meanwhile, for carbon membrane prepared under argon environment, the highest CO2/CH4 and CO2/N2 selectivity of 87.30 and 79.69, respectively, was achieved. The result indicated that the performance of the carbon tubular membrane can be controlled by varying the carbonization environment.